2004
DOI: 10.1063/1.1642583
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the proton tunneling splitting of the vinyl radical in the ground state by millimeter-wave spectroscopy combined with supersonic jet expansion and ultraviolet photolysis

Abstract: The vinyl radical in the ground vibronic state produced in a supersonic jet expansion by 193 nm excimer laser photolysis of vinyl bromide was investigated by millimeter-wave spectroscopy. Due to the proton tunneling, the ground state is split into two components, of which the lower and higher ones are denoted as 0+ and 0-, respectively. Eight pure rotational transitions with Ka = 0 and 1 obeying a-type selection rules were observed for each of the 0+ and 0- states in the frequency region of 60-250 GHz. Tunneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 41 publications
8
48
1
Order By: Relevance
“…The final results are Á 0 ðHÞ ¼ 0:14 cm À1 and Á 0 ðHÞ ¼ 0:53 cm À1 by the MP2/6-31G(d,p) and the CCSD(T)/aug-cc-pVTZ method, respectively. The converged result, Á 0 ðHÞ ¼ 0:53 cm À1 , is in good agreement with the experimental value, Á 0 ðHÞ ¼ 0:54 cm À1 [103]. This guarantees the accuracy of the present semiclassical theory at least for the ground vibrational state.…”
Section: Numerical Applicationssupporting
confidence: 75%
See 1 more Smart Citation
“…The final results are Á 0 ðHÞ ¼ 0:14 cm À1 and Á 0 ðHÞ ¼ 0:53 cm À1 by the MP2/6-31G(d,p) and the CCSD(T)/aug-cc-pVTZ method, respectively. The converged result, Á 0 ðHÞ ¼ 0:53 cm À1 , is in good agreement with the experimental value, Á 0 ðHÞ ¼ 0:54 cm À1 [103]. This guarantees the accuracy of the present semiclassical theory at least for the ground vibrational state.…”
Section: Numerical Applicationssupporting
confidence: 75%
“…14). Very recently, Tanaka et al [103] investigated this radical by millimeter-wave spectroscopy and reported a set of precise molecular constants together with the tunneling splitting. This fiveatom molecule is a good example so that we can accomplish the full-scale high level quantum chemical calculations and confirm the accuracy of our semiclassical theory of tunneling splitting.…”
Section: Numerical Applicationsmentioning
confidence: 99%
“…The Hamiltonian used in the analysis is that for an asymmetric top radical in a doublet state including the energy separation between the tunnelling levels, that is to say, no interaction terms connecting the two tunnelling substates were needed to account for the observed spectrum: H = H rot + H sr + H ns + H 01 . Details on these terms can be found in Tanaka et al (2004). Briefly, H rot and H sr stand for the Watson A reduction in the I r representation of the rotational and of the electron-spin rotational coupling tensors, respectively, both including the centrifugal distortion effects.…”
Section: Spectral Analysismentioning
confidence: 99%
“…Although we could not determine the ␦a F value of H 2 CCH in the previous study, 12 it should be similar to that in H 2 CCD. However, the mixing of para and ortho levels would be much smaller ͑about 0.00043%͒ than in deuterated species, because of large energy differences corresponding to ⌬E 0 = 16 272 MHz.…”
Section: ͑2͒mentioning
confidence: 55%
“…The energy separation between 0 + and 0 − is denoted by ⌬E 0 . Previously, 12 we observed millimeter-wave transitions connecting the 0 + and 0 − states of H 2 CCH to determine the tunneling splitting ⌬E 0 as 16 271.8429͑59͒ MHz. For this tunneling molecule, the molecular symmetry group C 2v ͑M͒ is appropriate, and the ground electronic state belongs to the 2 B 2 species of this group.…”
mentioning
confidence: 98%